Gendered Opportunity and School-Based Victimization: An Integrated Approach - Peterson, Samuel (Youth violence and juvenile justice, 2018)
Opportunity theory suggests that adolescents’ risks for school-based theft and assault victimization are related to low self-control and school-based routine activities, such as playing sports, joining extracurricular clubs, and engaging in unsupervised activities. Peer research indicates that friends’ characteristics may also create opportunities for victimization. Additional research supports that gender moderates the effects that lifestyles and friends have on victimization. We integrate these lines of inquiry by exploring how gender moderates the relationship among low self-control, routine activities, friends’ characteristics, and school-based victimization using a sample of 10th-grade public school students who participated in the Education Longitudinal Study of 2002. Using structural equation models, our results suggest that friends’ characteristics tend to matter more for females across both types of victimization. Other gendered effects exist—indicating that the effects of certain friends’ characteristics vary by gender according to the extent to which they influence participation in school misconduct.